Portable Water Shortages on Households in Bomaka in the Buea Municipality, South West Region of Cameroon: Challenges and Coping Strategies - Awudu, Ngwani; Nformi, Roland; Godlove, Funwi; Randy, Yinkfu (International Journal of Global Sustainability, 2023)
Today, in most urban areas in Sub-Saharan Africa, dwellers are facing difficulties in adequately accessing potable water in sufficient quantity and quality for their daily needs and uses. Analogously, there have been fledgling challenges triggered by portable water Shortage in Bomaka. This study aims to assess the problem of potable water accessibility in Bomaka in the Buea Municipality and the coping strategies developed by dwellers to meet their needs. The study used exploratory, inferential and descriptive research approaches. In this light, the cross-sectional research design was adopted to address the overall problem. A preliminary reconnaissance survey was accomplished whereby questionnaire and interview guides were administered. A total of 200 households were selected and investigated based on purposive and systematic random sampling, particularly around the water points. Secondary information was sought from published and unpublished materials. Results reveal that in Bomaka 100% of the households sourced their water from alternative sources (boreholes, wells, streams and springs) without any pre-treatment. Most of these sources do not flow regularly because of siltation or a drop in the volume of flow, especially in the dry season. The Cameroon Water Utilities Corporation (CAMWATER) is absent in this locality. Results also revealed that water sources were located at reasonable distances. This study records that the major causes of portable water shortages were population increase, poor planning and water pollution. The implications of irregular and portable water shortages are increased health risks, poor hygienic condition, disruption of economic activities and domestic routines. The study concludes that water remains the yard stick and a panacea to many countries and households. Thus, adequate planning, undivided attention and holistic measures should be implemented in order to sustain its accessibility.